Time Motion Analysis of Emergency Physician Workload in Urgent Care Settings. - Odorizzi, Scott; Hogan, Jessica; Idris, Sabrain; Marzano, Loraina; Rowley, Veronique; Yan, Max; Zhang, Yuxin; Perry, Jeffrey J. (Western Journal of Emergency Medicine: Integrating Emergency Care with Population Health, 2025)
Introduction: The Predictors of Workload in the Emergency Room (POWER) study, published in 2009 using data from 2003, examined the workload of emergency physicians using the Canadian Triage and Acuity Scale (CTAS) as a surrogate marker. Many hospitals use a case-mix formula incorporating annual census and POWER's study data to determine staffing levels. However, significant changes in emergency medicine have occurred since its publication, including the implementation of electronic health record systems, increased patient complexity, real-time dictation software, and human health resource challenges due to the COVID-19 pandemic. In this study we aimed to quantify the time required to perform tasks during the care of ambulatory emergency department (ED) patients. Our secondary objective was to stratify these times based on CTAS and clinician factors. Methods: We conducted a prospective observational time-motion study in the urgent care section of a tertiary-care, academic ED with 90,000 visits annually, 70% of which are ambulatory. Research assistants shadowed physicians on two 8-hour shifts daily (8 am-12 am) from July 12--August 14, 2022, tracking the time taken by physicians to perform tasks. We calculated aggregate task times per patient. Results: We observed 1,204 patient encounters over 65 shifts by 37 unique physicians. The mean treatment time was 21.6 minutes (95% confidence interval [CI] 19.9 - 23.3) for ambulatory CTAS 2 patients; 22.5 minutes (95% CI 21.2 - 23.6) for CTAS 3 patients; 19.7 minutes (95% CI 17.9 - 21.6) for CTAS 4 patients; and 17.4 minutes (95% CI 14.9 - 19.9) for CTAS 5 patients. Compared to the previous 2003 POWER study data, CTAS 4 and 5 patient assessment times took 31% and 58% longer, respectively. Total assessment time by CTAS was statistically significant only comparing CTAS 5 patients to all others (P = .02). Physicians who dictated their charts spent 34% less time (2.1 minutes per patient) charting than those who typed them. Conclusion: The average time to see an ambulatory ED patient was 21.7 minutes. Low-acuity urgent care patients take longer to assess now than 20 years ago. The CTAS alone is a poor marker of workload for ambulatory patients, necessitating a reassessment of staffing and compensation formulas.